Stripe phases - possible ground state of the high-Tc superconductors: General Aspects - Raczkowski, Marcin; Oleś, Andrzej M.; Frésard, Raymond (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
Based on the mean-field method applied either to the extended single-band Hubbard model or to the single-band Peierls-Hubbard Hamiltonian we study the stability of both site-centered and bond-centered charge domain walls. The difference in energy between these phases is found to be small. Therefore, moderate perturbations to the pure Hubbard model, such as next nearest neighbor hopping, lattice anisotropy, or coupling to the lattice, induce phase transitions, shown in the corresponding phase diagrams. In addition, we determine for stable phases charge and magnetizationdensities, double occupancy, kinetic and magnetic energies, and investigate the role of a finite electron-lattice coupling. We also review experimental signatures of stripes in the superconducting copper oxides.